MENINGKATKAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI METODE PEMBELAJARAN CURAH PENDAPAT(BRAINSTORMING) - Sapuan, - (WAHANA PEDAGOGIKA, 2016)
This study was aimed to determine the effect of brainstorming learning method to increase the ability of responding to something with the reasons on six graders of the Third state elementary school of Lopang, KembangbahuÂ  - Lamongan in the academic year of 2015/2016. This research was a classroom action research (PTK) with a teacher and all six graders of the Third state elementary school of Lopang, KembangbahuÂ  - Lamongan in the academic year of 2015/2016 as the data source. The results showed that at the first cycle there were 4 students with individual learning completeness of 12 students (33.33%), it showed that in this cycle has not experienced in classical completeness yet. At the second cycle there were 11 students who experienced in learning completeness individuals of 12 students (91.67%), it showed that in this cycle already experienced in classical completeness. And an increase in the average value of students is 65 in the first cycle to 76.67 in the second cycle. Thus, it could be concluded that there were significant learning method of brainstorming to increase the students ability in learning Sosial Science ( IPS).